Publications on operating room nursing in the period from 1980 to 2002 - Silva, Viviane Martins da (2003)
It was aimed at to identify the knowledge published in articles indexed in the data base LILACS on the theme Nursing in Surgical Center in the period from 1980 to 2002. They were 60 articles that were organized in the following categories: Attendance of Nursing that embraced the attendance to the adult population; Roles of Nurse in the Surgical Center, that treated of the assistant and the manager role; Nursing Education that included the teaching experiences with academics; Worker’s Health that pondered articles about problems or factors that affect the health of the nursing team; and the category Others that it embraced a small number of articles on specific thematic. It was ended that there is need to enlarge the studies on other clienteles and nuances of the thematic.